Experimental bond tests on masonry panels strengthened by FRP. (October 2015) - Mazzotti, Claudio; Ferracuti, Barbara; Bellini, Alessandro
Abstract: The results of an experimental campaign on bond between Glass Fiber Reinforced Polymer (GFRP) sheets and single clay brick or masonry panel is presented. Four different types of clay bricks (new and ancient) are considered, where the difference between bricks is not only due to their mechanical properties but also to their surface texture. Another focus point of the experimental campaign is the effect of mortar joints on the GFRP-masonry panel bond. Moreover, the effects of different surface preparations on the debonding load were investigated, concerning both bricks and masonry panels. A total number of 38 specimens was tested and results in terms of debonding force, strain along the GFRP and failure modes are here reported. The experimental results were also compared to design formula proposed by the new version of Italian Guidelines. Furthermore, in order to numerically describe the bond behaviour of the specimens tested, non-linear interface laws were calibrated starting from the debonding load and the measured strains along the GFRP for various loading levels.